PERANCANGAN RUANG BERMAIN DAN BERSANTAI YANG MENCIPTAKAN KEBAHAGIAAN - Illona Delarosa Widjaja; Franky Liauw (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
As the time goes by, humans’ daily activities predicted will be denser and could inflict some problems which built by negative emotion that occurs form human stress. This matter become concerned in a concept of dwelling in the future, which is how human survive. Humans in matter of survival, need some necessities. Those needs are fulfilled by human for releasing any negative emotions and gainning positive emotions or happiness. Therefore, this project is intended to fulfill happiness by proposing programs for playing and relaxing in leisure time for people around or outside the area. Those programs are based by some theories and understandings about happiness and which are being applied into architecture. In this case, placing and function of the space and also circulation are being thought out dynamically and based on hierarchy on the mass with the point of interest in playing and relaxing. This project is hoped for visitors who are coming could release stress and feeling happy. Keywords:  dwelling; emotion; happiness; play; relaxing AbstrakSeiring berkembangnya zaman, rutinitas manusia akan semakin padat dan dapat menimbulkan masalah dalam hal ini emosi negatif yaitu stres dalam diri manusia. Hal ini menjadi perhatian dalam konsep berhuni di masa depan, yaitu bagaimana manusia bertahan hidup. Manusia bertahan hidup memerlukan beberapa kebutuhan. Kebutuhan-kebutuhan tersebut dipenuhi manusia untuk mengeluarkan emosi negatif dan mendapatkan emosi positif. Karena itulah proyek ini bertujuan untuk memenuhi rasa bahagia tersebut dengan menyuguhi program-program untuk bermain dan bersantai di waktu luang bagi masyarakat sekitar kawasan atau luar kawasan. Program-program tersebut diwujudkan dari beberapa teori dan pemahaman tentang kebahagiaan yang lalu diaplikasikan ke dalam arsitektur. Dalam hal ini, penempatan dan fungsi ruang dan juga sirkulasi diciptakan secara dinamis dan berdasarkan hierarki pada massa bangunan dengan berlandaskan tujuan untuk bermain dan bersantai. Proyek ini diharapkan agar dapat membuat pengunjung melepas stres dan merasa bahagia.